NAD-Glycohydrolase Depletes Intracellular NAD+ and Inhibits Acidification of Autophagosomes to Enhance Multiplication of Group A Streptococcus in Endothelial Cells - Hsieh, Cheng-Lu; Huang, Hsuan-Min; Hsieh, Shu-Ying; Zheng, Po-Xing; Lin, Yee-Shin; Chiang-Ni, Chuan; Tsai, Pei-Jane; Wang, Shu-Ying; Liu, Ching-Chuan; Wu, Jiunn-Jong (Frontiers in Microbiology, 2018)
Group A Streptococcus (GAS) is a human pathogen causing a wide spectrum of diseases, from mild pharyngitis to life-threatening necrotizing fasciitis. GAS has been shown to evade host immune killing by invading host cells. However, how GAS resists intracellular killing by endothelial cells is still unclear. In this study, we found that strains NZ131 and A20 have higher activities of NADase and intracellular multiplication than strain SF370 in human endothelial cells (HMEC-1). Moreover, nga mutants of NZ131 (SW957 and SW976) were generated to demonstrate that NADase activity is required for the intracellular growth of GAS in endothelial cells. We also found that intracellular levels of NAD+ and the NAD+/NADH ratio of NZ131-infected HMEC-1 cells were both lower than in cells infected by the nga mutant. Although both NZ131 and its nga mutant were trapped by LC3-positive vacuoles, only nga mutant vacuoles were highly co-localized with acidified lysosomes. On the other hand, intracellular multiplication of the nga mutant was increased by bafilomycin A1 treatment. These results indicate that NADase causes intracellular NAD+ imbalance and impairs acidification of autophagosomes to escape autophagocytic killing and enhance multiplication of GAS in endothelial cells.